Impact of the IL-17F, IL-23 and IL-23R on susceptibility and phenotype of systemic lupus erythematosus. (17th August 2016) - Paradowska-Gorycka, Agnieszka; Sowinska, Anna; Stypinska, Barbara; Grobelna, Malwina Katarzyna; Walczyk, Marcela; Olesinska, Marzena; Piotrowski, Piotr; Jagodziński, Paweł Piotr
Abstract: Systemic lupus erythematosus (SLE) is a disease characterized by excessive proinflammatory cytokine production and damage to multiple organ systems. To investigate the potential association between cytokine gene polymorphisms and SLE, we performed a case-control study based on Polish population. SLE patients and controls, were examined for IL-23A rs11171806 G/A and IL-23R (rs1884444 G/T, rs10489629 G/A) by TaqMan SNP genotyping assay, for IL-17F rs763780 A/G and rs2397084A/G using the PCR– RFLP method. An increased frequency of AG genotype as well as G allele of the IL-17F rs763780 was found in patients with SLE, as compared with healthy subjects (OR = 3.947; p = 0.001 and OR = 3.538; p = 0.002, respectively). Frequencies of the rs1884444 TT genotype (OR = 138.1) and the rs1884444 T allele (OR = 2.176) were also higher in SLE patients (both p < 0.0001). Overall, weak LD was observed between the IL-17F rs763780 A/G and rs2397084 A/G polymorphisms ( D '-0.003, r 2 – 0.000). From four possible haplotypes, frequencies of AG showed differences between both examined groups ( p < 0.0001). We also observed a weak LD between the IL-23R rs10489629G/A and rs1884444 G/T ( D '-0.199, r 2 –0.026). The genotype–phenotype analysis showed significant association between the IL-17F rs2397084 and mean value of the hemoglobin ( p = 0.01), the IL-17F rs763780 and age ( p = 0.008) and lupus anticoagulant ( p = 0.09), the IL-23 rs11171806 and urea ( p = 0.08) and C3 complement ( p = 0.03), and the IL-23R rs1884444 G/T and activated partial thromboplastin time ( p = 0.06). Present findings indicated that IL-17F rs763780 A/G and IL-23R rs1884444 G/T polymorphisms may be involved in susceptibility to SLE in the Polish population.